(untitled) - Davis, Kathryn (Boston, 2002)
Davis (The Girl Who Trod on a Loaf) offers a short but poignant meditation on the life of Marie Antoinette and the role of fate in our lives. Much has been written about that queen, but this novel is unique, using Versailles and its Hall of Mirrors as much more than just a building and a room. Versailles was built to reflect the glory and power of Louis XIV, but by the end of the 18th century it had become a cocoon sheltering its inhabitants in a beautiful but artificial world. At the age of 14, Marie leaves her Austrian homeland to join her fiance, the eventual Louis XVI. Never quite at home in France and never really accepted by her subjects, she finds solace in Versailles itself. She flits from room to room, from circumstance to circumstance, unaware of the symbol she has become until it is too late. The portrait that emerges is of a woman hemmed in by fate and her own na‹vet‚, who has her faults but who is nonetheless courageous and devoted to her family. Told from Marie's perspective, this is a refreshing change of pace from the typical historical novel and is highly recommended to all public and most academic libraries. David W. Henderson, Eckerd Coll. Lib., St. Petersburg, FL
Keywords: Queens,History,Château de versailles (versailles, france),Versailles (france),Marie antoinette queen, consort of louis XVI, king of france, 1755-1793; Fiction,Hiction,Louis XVI,Fiction,Fiction,Fiction; 1774-1793; France